A cognitive approach for evaluating the usability of Storage as a Service in Cloud Computing Environment - Sharmistha Roy; Prasant Kumar Pattnaik; Rajib Mall (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Cloud computing is a style of computing which thrives users requirements by delivering scalable, on-demand and pay-per-use IT services. It offers different service models, out of which Storage as a Service (StaaS) is the fundamental block of Infrastructure cloud that fulfills user’s excess demand of elastic computing resources.  But considering the competitive business scenario choosing the best cloud storage provider is a difficult task. Thus, usability is considered to be the key performance indicator which evaluates the better cloud storage based on user’s satisfaction. This paper aims to focus on the usability evaluation of StaaS providers namely Google drive, Drop box and One drive. This paper proposed a fuzzy based AHP model for measuring user satisfaction. Usability evaluation is carried out based on user feedback through Interview and Questionnaire method. Analysis of user feedback is done based on the fuzzy approach in order to remove vaguness. Whereas, AHP model is used for measuring satisfaction degree of the different cloud storage services and it solves the problem of selecting best cloud storage.